Impact of subgrid‐scale processes on eyewall replacement cycle of tropical cyclones in HWRF system. Issue 22 (19th November 2015) - Zhu, Ping; Zhu, Zhenduo; Gopalakrishnan, Sundararaman; Black, Robert; Marks, Frank D.; Tallapragada, Vijay; Zhang, Jun A.; Zhang, Xuejin; Gao, Cen
Abstract: Two idealized simulations by the Hurricane Weather Research and Forecast (HWRF) model are presented to examine the impact of model physics on the simulated eyewall replacement cycle (ERC). While no ERC is produced in the control simulation that uses the operational HWRF physics, the sensitivity experiment with different model physics generates an ERC that possesses key features of observed ERCs in real tropical cyclones. Likely reasons for the control simulation not producing ERC include lack of outer rainband convection at the far radii from the eyewall, excessive ice hydrometeors in the eyewall, and enhanced moat shallow convection, which all tend to prevent the formation of a persistent moat between the eyewall and outer rainband. Less evaporative cooling from precipitation in the outer rainband region in the control simulation produces a more stable and dryer environment that inhibits the development of systematic convection at the far radii from the eyewall. Key Points: Eyewall replacement cycle (ERC) is simulated by HWRF Sensitivity of ERC to model physics is investigated Ice‐phase and warm rain microphysics have a profound impact on ERC